A hybrid method for X‐ray optics simulation: combining geometric ray‐tracing and wavefront propagation. (15th May 2014) - Shi, Xianbo; Reininger, Ruben; Sanchez del Rio, Manuel; Assoufid, Lahsen
<x xml:space="preserve">Abstract</x> A new method for beamline simulation combining ray‐tracing and wavefront propagation is described. The `Hybrid Method' computes diffraction effects when the beam is clipped by an aperture or mirror length and can also simulate the effect of figure errors in the optical elements when diffraction is present. The effect of different spatial frequencies of figure errors on the image is compared with SHADOW results pointing to the limitations of the latter. The code has been benchmarked against the multi‐electron version of SRW in one dimension to show its validity in the case of fully, partially and non‐coherent beams. The results demonstrate that the code is considerably faster than the multi‐electron version of SRW and is therefore a useful tool for beamline design and optimization.